Research on risk inclination of young female athletes in the dimensions of life orientations - Tavrovetska, N.; Popovych, I.; Savchuk, O.; Piletsk, L.; Lappo, V.; Abramian, N.; Zahrai, L. (Journal of Physical Education and Sport, 2023)
Purpose of the study is to conduct empirical research and theoretically substantiate the impact of the parameters of life orientations (dispositional optimism, positive and negative expectations) on risk inclination of young female athletes. The sample of research participants involved representatives of six teams from different regions of Ukraine in team (Group 1) and individual sports (Group 2): handball (n=61; 59.80%) and track and field (n=41; 40.20%). The respondents included representatives of the Championship of Ukraine (Junior League) and regular participants of International, European and World sports competitions as members of the national team of Ukraine. Methods: valid psycho-diagnostic instruments, test of Kruskal-Wallis, Spearman`s correlation coefficient (rs) and Mann-Whitney U-test. Results. It was established that Group 1 has an advantage over Group 2 by the parameters of risk inclination: emotional inclination (H=13.683; p<.001), controlling-regulating inclination (H=9.997; p=.002) and by the parameter of life orientations - positive expectations (H=3.998; p=.046). It was established and substantiated that the parameters of life orientations of young female athletes are the factors determining the motive for achieving success and affecting risk inclination. The strongest positive correlations of negative expectations with the assessment of risk inclination (rs=.685; p<.010) and motivation for achieving success (rs=.425; p<.010) are an evidence of excessive, immoderate aspiration to achieve a desirable result, which can lead to instant, phenomenal success, or failure, disappointment and even physical and psycho emotional traumas. On the contrary, moderate mindset, systemic training, improving tactical-technical actions and personal technical mastery reinforce positive expectations and boost dispositional optimism, contributing to young athletes` understanding that they are on the right track and their victory is inevitable. There were statistically significant differences in the respondents in the comparison of a low level (Group I) and a high level of dispositional optimism (Group II) in a number of parameters. The study substantiated that a high level of dispositional optimism is orientation towards cognitive and behavioral risk inclination accompanied by positive and negative expectations with dominance of motivation for achieving success. Conclusions. We generalized that the parameters of life orientations affect risk inclination of young female athletes. Motivation for achieving success and avoiding failure and risk inclination are predictors of life orientations of young female athletes, designing their career in sports. The obtained results should be taken into consideration by trainers working with young female athletes.